Creationism and intelligent design are incompatible with scientific progress: A response to Shanta and Vêdanta?. Issue 1 (2nd January 2016) - Caetano-Anollés, Gustavo
ABSTRACT: In a recent opinion paper, B.K. Shanta claims science leaves no room for the subjective aspect of consciousness, and in doing so, attacks both origin of life and evolutionary research. He claims Vêdanta, one of the 6 orthodox schools of Hindu philosophy, offers an explanation: "the origin of everything material and nonmaterial is sentient and absolute." Here I discuss how the pseudoscience of these creationist views, which are aligned with Intelligent Design, are incompatible with scientific progress and should not be published in scientific journals.